Android-based Serli E-Module (Seroid E-Module) on Solar System Material for Sixth-Grade Elementary School Students - Melyani Sari Sitepu; Azizah; Astri Dwi Wulandari (Universitas Pendidikan Ganesha, 2023)
Learning solar system material for elementary school students is still carried out using printed textbooks. The lack of media use then impacts low motivation and student learning outcomes. This study aims to create electronic learning media in the form of an Android-based Serli module (E-Module Seroid) on solar system material. This research belongs to the type of development research which was developed using the ADDIE model. The subjects involved in this study consisted of 6 students in the small trial and 20 in the field trial. Data collection was carried out using the method of observation, interviews, questionnaires, and tests, with research instruments in the form of observation sheets, questionnaire sheets, and multiple-choice tests. The research data were then analyzed qualitatively and quantitatively. Qualitative data analysis was carried out with central tendency and data categorization—quantitative data analysis with the Wilcoxon test. The study results obtained a media validation value of 84 or very valid. Material validation is 87.5 or very valid. The practical result is 89.6, or very practical. The Wilcoxon test results obtained a significant value of 0.001. It means that the seroid module is effectively used in learning. The data analysis concluded that the android-based serli e-module (Seroid E-module) in the solar system material was valid, practical, and effective for sixth-grade elementary school students.